Experience of Successful Operation on Chronic Idiopathic Intestinal Pseudo-obstruction Syndrome Associated with Von Recklinghausen's Disease - Orita, Taizo; Matsumoto, Mitsuaki; Nakai, Hajime; Orita, Yojiro; Harafuji, Izumi; Kasahara, Junji; Kobayashi, Naoya; Tanakaya, Koji (Nippon Shokaki Geka Gakkai zasshi, 1992)
A 28-year-old man with the symptoms of ileus was admitted to our hospital. Though we suspected Von Recklinghausen's disease, there was no past history of laparotomy. A barium contrast study of the gastrointestinal tract revealed an abnormally dilated image from the duodenal bulb to the Treitz's ligament. Because it was impossible to find the cause of and then improvement in the symptoms of the ileus, we conducted an exploratory laparotomy withouta clear reason. But, we could not find any lesion that caused ileus. Therefore, from the operative findings and clinical progress, we diagnosed this case as chronic idiopathic intestinal pseudo-obstruction syndrome. After approximately 8 months of conservative treatment, a bypass operation on the gastrointestinal tract was performed (jejuno-jejunostomy, jejuno-cecostomy, jejunostomy) for relief of the symptoms of ileus. After the operation, thispatient was permitted to resume normal daily living and has had no relapses of the symptoms of ileus. The operation may be a critical treatment for this intractable disease whose treatment has not yet been established, but we expect a bypass operation on the gastrointestinal tract to become a useful method of treatment. Including this case, 48 cases in Japanwere reviewed.